Experimental Study on Refrigeration System of Phase-change Energy Storage for High-power Applications - Yuan Junfei; Wang Lin; Tan Yingyin; Jiao Yonggang (Zhileng xuebao)
To meet the cooling system requirements of intermittent high-power electronic equipment, we investigated a cascade cooling system with a phase-change energy storage that is based on a traditional R134a vapor-compression cycle cascaded with a mechanicalpump cycle. The operating principle and refrigerant features were theoretically analyzed and the operating characteristics of an energy storage device were reviewed in this research. The cooling capacity and operating performance of the system were experimentally measured during its start-up and stable operation. The main conclusions drawn from this study were that at the startup stage of the mechanical pump, the system pressure first decreased and then increased by an amplitude of 30 kPa. When the heat source started up, the system pressure first increased then decreased and remained stable. It was determined that the accumulator can effectively store the excess working medium of the system and indirectly control the phase change temperature and pressure in the heat sink. Furthermore, the energy storage device can maintain a mechanical pump inlet super cooling degree of 5 ℃ in the system operation process. The energy storage device can also meet the demand of the heat load and maintain 5 ℃ of super cooling before the working fluid is interred in the mechanical pump, indicating that this device was reasonably designed and its operation stable. Although the cooling capacity of the refrigeration system reduced gradually with the running time, it was able to run for 5 minutes with a heat load of more than 10kW, thus meeting the design requirements of the subject.